2018
DOI: 10.1056/nejmoa1805131
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockade with Cemiplimab in Advanced Cutaneous Squamous-Cell Carcinoma

Abstract: Among patients with advanced cutaneous squamous-cell carcinoma, cemiplimab induced a response in approximately half the patients and was associated with adverse events that usually occur with immune checkpoint inhibitors. (Funded by Regeneron Pharmaceuticals and Sanofi; ClinicalTrials.gov numbers, NCT02383212 and NCT02760498 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
1,026
3
43

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,115 publications
(1,100 citation statements)
references
References 24 publications
28
1,026
3
43
Order By: Relevance
“…In this context, the recent negative results of the randomized multicenter postoperative chemoradiation study in regionally metastatic HNcSCC were disappointing . However, recent studies evaluating immunotherapy demonstrate that cSCC has a high response rate to PD‐1/PD‐L1 blockade, and this treatment option may also be better suited to an aging population than platinum‐based chemotherapy . It is very likely that the next generation of adjuvant trials in HNcSCC will incorporate PD‐1/PD‐L1 immunotherapy in conjunction with adjuvant RT.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the recent negative results of the randomized multicenter postoperative chemoradiation study in regionally metastatic HNcSCC were disappointing . However, recent studies evaluating immunotherapy demonstrate that cSCC has a high response rate to PD‐1/PD‐L1 blockade, and this treatment option may also be better suited to an aging population than platinum‐based chemotherapy . It is very likely that the next generation of adjuvant trials in HNcSCC will incorporate PD‐1/PD‐L1 immunotherapy in conjunction with adjuvant RT.…”
Section: Discussionmentioning
confidence: 99%
“…For metastatic cSCC, immunotherapy is a promising first‐line treatment option. A recent study of PD‐1 blockade with cemiplimab in advanced cSCC reported a response in 47% of the patients . This may be a function of the expression of abundant neoantigens in cSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent individuals, cSCCs express a chemokine profile that facilitates recruitment of immune cells into the TME, but multiple mechanisms within the TME suppress their function including expression of immune checkpoints. Accordingly, half of all patients bearing advanced or recurrent/metastatic cSCCs demonstrate objective responses to PD‐1 mAb treatment . This highly inflamed phenotype is also observed in other SCCs, such as HNSCC where ΔNp63α is frequently overexpressed …”
Section: Cross Talk Between the Nf‐κb And P63 Families Influences Thementioning
confidence: 89%